Exploring the horror of supernatural fiction : Ray Bradbury's Elliott family - Concoran, Miranda; Ellerhoff, Steve Gronert (New York, NY : Routledge, 2020)
Detailing the adventures of a supernatural clan of vampires, witches, and assorted monstrosities, Ray Bradbury's Elliott family stories are a unique component of his extensive literary output. Written between 1946 and 1994, Bradbury eventually quilted the stories together into a novel, From the Dust Returned (2001), making it a creative project that spanned his adult life. Not only do the stories focus on a single familial unit, engaging with overlapping twentieth-century themes of family, identity and belonging, they were also unique in their time, interrogating post-war American ideologies of domestic unity while reinventing and softening gothic horror for the Baby Boomer generation. Centred around diverse interpretations of the Elliott Family stories, this collection of critical essays recovers the Elliotts for academic purposes by exploring how they form a collective gothic mythos while ranging across distinct themes. Essays included discuss the diverse ways in which the Elliott stories pose questions about difference and Otherness in America; engage with issues of gender, sexuality, and adolescence; and interrogate complex discourses surrounding history, identity, community, and the fantasy of family.
OCLC-licensed vendor bibliographic record.
Keywords: Bradbury, Ray, -- 1920-2012 -- Criticism and interpretation; Supernatural in literature; LITERARY CRITICISM / General